Field reports form for submitting seasonal observations of Iowa birds, Francis L. Moore, spring 1988 - Moore, Francis L.et al (1988)
List of birds and locations contributed by Francis L. Moore with observers Carl J. Bendorf, Thomas H. Kent, Dick Tetrault and W. Ross Silcock. The field notes include details on five species of birds sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1988. Epson - sheet feed